2015
DOI: 10.1371/journal.pone.0122024
|View full text |Cite
|
Sign up to set email alerts
|

Tang-Nai-Kang Alleviates Pre-diabetes and Metabolic Disorders and Induces a Gene Expression Switch toward Fatty Acid Oxidation in SHR.Cg-Leprcp/NDmcr Rats

Abstract: Increased energy intake and reduced physical activity can lead to obesity, diabetes and metabolic syndrome. Transcriptional modulation of metabolic networks has become a focus of current drug discovery research into the prevention and treatment of metabolic disorders associated with energy surplus and obesity. Tang-Nai-Kang (TNK), a mixture of five herbal plant extracts, has been shown to improve abnormal glucose metabolism in patients with pre-diabetes. Here, we report the metabolic phenotype of SHR.Cg-Lepr c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Tang-Nai-Kang is a mixture of five herbal plant extracts that has been shown to improve glucose metabolism abnormalities in patients with pre-diabetes. Tang-Nai-Kang treatment can deacetylate PGC1α to activate it and synergize with PPAR expression to enhance fatty acid oxidation and improve insulin levels in rats (Li et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Tang-Nai-Kang is a mixture of five herbal plant extracts that has been shown to improve glucose metabolism abnormalities in patients with pre-diabetes. Tang-Nai-Kang treatment can deacetylate PGC1α to activate it and synergize with PPAR expression to enhance fatty acid oxidation and improve insulin levels in rats (Li et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In the DIO experiment, the Tg mice were provided a high-fat (HF) diet (D12492: 60% kcal% fat; Research Diets, New Brunswick, NJ, USA) starting from when they were 9 wk old; after 12 wk, tissue and blood samples were collected and stored at 280°C or fixed in 4% paraformaldehyde in PBS. Body composition of mice was evaluated through multifrequency bioelectrical impedance analysis performed using an ImpediVet (ImpediMed, Brisbane, QLD, Australia) according to the manufacturer's instructions, as previously described by Li et al (23). Unless otherwise noted, male mice were used in this study.…”
Section: Animalsmentioning
confidence: 99%
“…e significant path is the green round. Evidence-Based Complementary and Alternative Medicine resistance [11]. Another research of Jiangtang Xiaozhi, which comprised six commonly used herbs, found that 16 weeks of Jiangtang Xiaozhi treatment did not lower fasting blood glucose, but it improved FINS and HDL cholesterol in a Western population with prediabetes or controlled diabetes [24].…”
Section: Discussionmentioning
confidence: 99%
“…KEGG analysis of the weighted coexpression networks of ncRNA and mRNA and ceRNA indicated that 22 pathways were significantly enriched. PPAR pathway [11], fatty acid metabolism [25], and nitrogen metabolism [26] have been reported to be related to T2DM. Usually, a certain miRNA may have multiple different mRNA targets, whereas a given target gene may also be targeted by multiple miRNAs [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation